1988
DOI: 10.1002/gepi.1370050609
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of acute lymphoblastic leukemia with HLA‐Cw7

Abstract: Frequencies of all defined HLA-A, -B, -C (-DR) antigens were determined in 142 (59) Germans suffering from acute lymphoblastic leukemia (ALL) with differentiation of immunologically defined or age-related subgroups of the disease. A highly significant rise of the HLA-C locus antigen Cw7 was found in ALL patients, particularly those over the age of 11 in comparison with local German and Caucasian controls of the Ninth Int. Histocompatibility Workshop (WS). Only slight differences of HLA-Cw7 frequencies were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…The independent determination of the JY328, HLA-4, and Cw7 sequences in different laboratories (38,40,43) gives confidence to the validity of this unique set of linked substi-tutions; furthermore, they have also been found in gorilla homologues of HLA-C (54). HLA-Cw7 is the most common HLA-C antigen in many human populations (2), having a frequency of '~40% in Caucasians, for example (22). Thus, the representation at the population level of the unusual Cw7 sequence is much greater than appreciated from simple comparisons in which alleles are given equal weight irrespective of frequency (55).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The independent determination of the JY328, HLA-4, and Cw7 sequences in different laboratories (38,40,43) gives confidence to the validity of this unique set of linked substi-tutions; furthermore, they have also been found in gorilla homologues of HLA-C (54). HLA-Cw7 is the most common HLA-C antigen in many human populations (2), having a frequency of '~40% in Caucasians, for example (22). Thus, the representation at the population level of the unusual Cw7 sequence is much greater than appreciated from simple comparisons in which alleles are given equal weight irrespective of frequency (55).…”
Section: Resultsmentioning
confidence: 97%
“…The functional capacity of the Cw3 molecule has also been examined in transgenic mice, and examples of mouse CTL recognizing both viral peptides presented by Cw3, and Cw3 as an alloantigen, were found (18). These results demonstrate that HLA-C molecules can participate in the immune response, a concept also supported by the association of HLA-C antigens with susceptibility to disease (19)(20)(21)(22)(23). Giissow et al (7), however, have suggested that "HLA-C may be dispensable for proper functioning of the immune system" and concerns as to the significance of the contribution of HLA-C to protective immunity compared with HLA-A and B remain (24,25).…”
mentioning
confidence: 85%
“…D'Amaro et al (1984 ) found significant relative risks of 2.97 and 2.10 for Cw3 and Cw4, respectively, in ALL, and Bortin et al (1987 ) confirmed this association in a larger number of patients in the same series. Müller et al (1988 ) subsequently reported a significant increase in Cw7 in c‐ALL patients over the age of 11 years (RR = 2.74), whilst De Moor et al (1988 ) and Caruso et al (1988 ) reported Cw3 and Cw4 associations with ALL. These results suggested that the association with more than one Cw allele could be due to the presence of sequences encoding NK1 or NK2 within exon 2 of the HLA‐C locus, since Cw3 and Cw7 both type for NK1, and Cw2 and Cw4 both type for NK2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous serological studies showed that at least three HLA‐Cw antigens (Cw3, Cw4 and Cw7) were associated with susceptibility to ALL ( D'Amaro et al , 1984 ; Bortin et al , 1987 ; Muller et al , 1988 ). This could be explained if the same functionally important molecular structure was encoded by more than one Cw allele.…”
mentioning
confidence: 99%
“…Muller et al (27) in a German study compared ALL patients (all ages) to two different control groups and found statistically significant associations with HLA-Cw7 even after correction for multiple comparisons. However, the association was less evident when restricted to patients less than aged 11 years.…”
Section: Classical Hla Genesmentioning
confidence: 99%